2021
DOI: 10.2147/jmdh.s343528
|View full text |Cite
|
Sign up to set email alerts
|

Outpatients’ Opinion And Experience Regarding Telepharmacy During The COVID-19 Pandemic: The Enopex Project

Abstract: Background Telepharmacy, as a remote pharmaceutical care procedure, is being used worldwide during the COVID-19 pandemic, with the aim of preserving the health of patients and professionals. Its future development should incorporate the assessment of patient perception, but no research study has investigated it. Objective The objective was to poll the opinions and experiences of outpatients with telepharmacy through a purpose-developed questionnaire and to assess it’s q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Among adult patients utilizing telepharmacy services in Spain during COVID-19, 96.7% reported being “satisfied” or “very satisfied” with their telepharmacy experiences. 33 Similarly high levels of satisfaction with telepharmacy have been found during COVID-19 among adult patients at specialized hospital clinics in Iran (77% favored telepharmacy while 23% favored in-person care), 34 and pre-COVID-19 among HIV outpatients undergoing treatment. 35 Telehealth, applying digital communications to deliver healthcare services remotely, and other virtual platforms have also demonstrated benefits for individuals with anxiety and depression.…”
Section: Discussionmentioning
confidence: 74%
“…Among adult patients utilizing telepharmacy services in Spain during COVID-19, 96.7% reported being “satisfied” or “very satisfied” with their telepharmacy experiences. 33 Similarly high levels of satisfaction with telepharmacy have been found during COVID-19 among adult patients at specialized hospital clinics in Iran (77% favored telepharmacy while 23% favored in-person care), 34 and pre-COVID-19 among HIV outpatients undergoing treatment. 35 Telehealth, applying digital communications to deliver healthcare services remotely, and other virtual platforms have also demonstrated benefits for individuals with anxiety and depression.…”
Section: Discussionmentioning
confidence: 74%
“…Patients are unfamiliar with or uncomfortable using technology and are concerned about the security and privacy of online interactions. These drawbacks have been previously pointed out by some studies [ 18 - 21 ]. This may explain why some people may not be aware of telepharmacy services or their benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Complete adherence to medication consultation advice by all users suggests that the telepharmacy service effectively conveyed information and instructions related to medication usage. Telepharmacy provides convenience by enabling users to receive pharmacy services from the comfort of their homes or preferred locations [ 18 ]. This can save time and reduce the hassle associated with traditional pharmacy visits.…”
Section: Discussionmentioning
confidence: 99%
“…Telepharmacy is a remote pharmaceutical care procedure. It has been used worldwide during the COVID-19 pandemic, with the aim of preserving the health of patients and professionals [ 21 ]. Dat et al reported that about 87% of pharmacists have used telepharmacy in their pharmacy practice in response to the COVID-19 pandemic in Ho Chi Minh City, Vietnam.…”
Section: Discussionmentioning
confidence: 99%